The Non-Property Personal Rights and Obligations of Parents Towards Children - Shestani, Anilda (European Journal of Multidisciplinary Studies, 2016)
Parental responsibility is already defined in the Family Code as “the totality of the rights and obligations that aimed to ensure emotional, social and material welfare of the child, taking care, maintaining personal relations with him, and assuring him welfare, education, legal representation and administration of his property”. In this paper will be analyzed the parental rights and obligations that exercised about the personality of the child that arise as a result of personal non-property relations. This set of rights and duties is different from the other groups of rights and obligations of parent exactly for the lack of their economic content. Parental rights and obligations are the same regardless of the source of birth of parental relationship, biological or declaration of the will on one side, or regardless of the status of children born from the marriage or outside it, on the other side. The concept of the relationship between parents and children has changed a lot from the past in the time that we live today. In the modern concept, parental authority in exercising the rights and obligations to children is conceived in the interest of minors implying therefore the idea of protection that parents are obligated towards their children. This paper will also show how the non-property personal rights and obligations of parents towards the children are applicable in the practice; what are the main problems that appeared during this process and best recommendations for an efficient exercise of these rights and obligations based on the best interest of the child.